Working Capital Management in Flower Retail Business - Talgat, Baidauletov (2010)
The purpose of this paper is to provide empirical evidence that working capital management plays significant role in small and medium sized firm and especially for flower retail business in Kazakhstan. The results of this investigation will be used in our flower retail network in Astana further business activity.